Peers To Professors: Exploring The Role Of Students And Faculty In Same-Level Reciprocal Peer Assisted Learning In Family Medicine Clerkship - Muneeza Aamir Sami; Lubna Ansari Baig; Saima Perwaiz Iqbal; Riffat Shafi; Sobia Parveen (Journal of Rawalpindi Medical College)
Objective: Peer-assisted learning (PAL) is teaching by the learners to the learners, a teaching strategy globally integrated into curricula. One particular variant is same-year reciprocal PAL, in which peer tutors and tutees are from the same academic year and alternate teaching roles. However, few studies have examined this specific form of PAL, and both student and faculty perspectives on its efficacy remain largely unexplored. To address this gap, we conducted a qualitative study among fourth-year medical students during their Family Medicine clerkship.